Embryonic Tumor with Abundant Neuroepithelium and True Rosettes (ETANTR): Case Report and Literature Review - Tavares, Cleciton Braga; Gomes-Braga, Francisca das Chagas Sheyla Almeida; Sousa, Emerson Brandão; Ferreira, Camilla Aniele Areia; Brito, José Nazareno Pearce de Oliveira (Arquivos Brasileiros de Neurocirurgia: Brazilian Neurosurgery, 2017)
The embryonal tumor with abundant neuropil and true rosettes (ETANTR) is an extremely rare variant of the primitive neuroectodermal tumor (PNET). About 80 cases have been reported since its first description in the literature, in 2000. The ETANTR occurs in very young patients, especially children under 6 years of age. It is found mainly in the cerebral cortex. Headache, focal neurological signs, seizures, increased head circumference and psychomotor developmental delay are the most frequent symptoms of ETANTR. Histologically, it displays the features of an ependymoblastoma and a neuroblastoma, showing areas of neuroepithelium fibrillar rosettes with ependymoblastic zones and interposed undifferentiated neuroepithelial cells. The ETANTR is distinguishable from other embryonal tumors due to the abundance of neuroepithelium. Genetic studies have demonstrated the presence of polysomy of chromosome 2 and chromosome 19q13.42 amplification. This is an extremely aggressive tumor with a mean survival ranging from 9 to 48 months. We present the first report in Brazil, published in indexed literature, of an ETANTR case involving a young child.
Keywords: primitive neuroectodermal tumors; ependymoblastoma; neuroblastoma